MIXUE'S SURABAYA BRAND IMAGE, PRODUCT QUALITY, BRAND LOVE AND LOYALTY INFLUENCE - Jonathan Felix Alfredo Samekto; Tuty Lindawati; Maria Mia Kristanti (Research In Management and Accounting (RIMA), 2023)
The purpose of this research is to test the influence analysis of Brand Image and Product Quality on Brand Love and Brand Loyalty Mixue in Surabaya. The sampling technique used non-probability sampling with purposive sampling method. The samples taken were 160 respondents who were consumers from Mixue in Surabaya. While the tools used to retrieve and collect data are in the form of online questionnaires via the Google form. The data analysis technique uses Structural Equations Modeling (SEM) using the LISREL program. The results of this study state that Brand Image has a positive and insignificant effect on Brand Love, Product Quality has a positive and significant effect on Brand Love, Brand Image has a negative and insignificant effect on Brand Loyalty, Product Quality has a positive and insignificant effect on Brand Loyalty, Brand Love has a positive and significant effect on Brand Loyalty.